Dingoes at dinnertime - Osborne, Mary Pope.; Murdocca, Sal (New York : Random House, 2000)
The magic tree house whisks Jack and Annie away to Australia where they must save some animals from a wildfire.
"A Stepping Stone book."
RL: 2.1.
006-009.
310
Accelerated Reader AR
Keywords: Magic -- Juvenile fiction; Space and time -- Juvenile fiction; Zoology -- Australia -- Juvenile fiction; Animals -- Juvenile fiction; Australia -- Juvenile fiction; Fantasy fiction